Recurrence patterns after radical hysterectomy in stage IB1- IIA cervical - Kriengkrai Sittidilokratna (2018)
Objectives: The purpose of this study was to evaluate the patterns of recurrence and its associated factors in stage IB1-IIA cervical cancer cases after radical hysterectomy. Methods: We retrospectively reviewed the 655 medical records of patients with cervical cancer who underwent radical surgery at Chiang Mai University Hospital between January 2003 and December 2006. All patients had a type III radical hysterectomy and complete systematic bilateral pelvic lymphadenectomy. Post-operative adjuvant pelvic radiation therapy was given concurrently with weekly cisplatin 40 mg/m2 for 6 cycles to patients with at least one major risk or two intermediate-risk factors. Sites of disease recurrence, time to relapse of disease, and postoperative overall survival were analyzed and all possible clinicopathological factors related to the risk of recurrence were determined. Results: The median time to recurrence was 11.5 months (range, 2-45 months). There was no significant differences in the mean time to recurrence between local and distant recurrence groups (14.6 ±3.9 months vs. 16.2±5.3 months; p=0.632). The 3-year survival rates of patients with local and distant recurrences were 67.6% (95%CI=45.6 to 89.6%) and 39.8% (95%CI=11.8 to 67.8%), respectively (p=0.602). Tumor size was the only clinicopathological prognostic factor associated with overall survival. Conclusion: Patients with stage IB1-IIA cervical cancer should have close surveillance during the first two years of radical surgery. Tumor size of greater than 2 cm at the time of primary surgery appears to be significantly related to the prognosis of patients with recurrence. With an understanding of the natural history of cervical cancer recurrence, an optimal method of follow-up and prospective clinical trial for markers of metastatic potential to detect recurrence need to be conducted in the future.